Comparison of the safety profile, conversion rate and hospitalization duration between early and delayed laparoscopic cholecystectomy for acute cholecystitis: a systematic review and meta-analysis - Wu, Hongsheng; Liao, Biling; Cao, Tiansheng; Ji, Tengfei; Huang, Jianbin; Luo, Yumei; Ma, Keqiang (Frontiers in Medicine, 2023)
Background: Although the past decade has witnessed unprecedented medical progress, no consensus has been reached on the optimal approach for patients with acute cholecystitis. Herein, we conducted a systematic review and meta-analysis to assess the differences in patient outcomes between Early Laparoscopic Cholecystectomy (ELC) and Delayed Laparoscopic Cholecystectomy (DLC) in the treatment of acute cholecystitis. Our protocol was registered in the PROSPERO database (registration number: CRD42023389238). Objectives: We sought to investigate the differences in efficacy, safety, and potential benefits between ELC and DLC in acute cholecystitis patients by conducting a systematic review and metaanalysis. Methods: The online databases PubMed, Springer, and the Cochrane Library were searched for randomized controlled trials (RCTs) and retrospective studies published between Jan 1, 1999 and Jan 1, 2022. Results: 21 RCTs and 13 retrospective studies with a total of 7601 cases were included in this research. After a fixed-effects model was applied, the pooled analysis showed that DLC was associated with a significantly high conversion rate (OR: 0.6247; 95%CI: 0.5115-0.7630; z=-4.61, p<0.0001) and incidence of postoperative complications (OR: 0.7548; 95%CI: 0.6197-0.9192; z=-2.80, p=0.0051). However, after applying a random-effects model, ELC was associated with significantly shorter total hospitalization duration than DLC (MD: -4.0657; 95%CI: -5.0747 to -3.0566; z= -7.90, p<0.0001). Conclusions: ELC represents a safe and feasible approach for acute cholecystitis patients since it shortens hospitalization duration and decreases the incidence of postoperative complications of laparoscopic cholecystectomy.